Research progress on the relationship between leaf senescence and quality, yield and stress resistance in horticultural plants - Zhao, Wenxue; Zhao, Huayuan; Wang, Huasen; He, Yong (Frontiers in Plant Science, 2022)
Leaf senescence, the final stage of leaf development, is one of the adaptive mechanisms formed by plants over a long period of evolution Leaf senescence is accompanied by various changes in cell structure, physiological metabolism, and gene expressions. This process is controlled by a variety of internal and external factors. Meanwhile, the genes and plant hormones involved in leaf aging affect the quality, yield and stress resistance in horticultural plants. Leaf senescence mediated by plant hormones affected plant quality at both pre-harvest and post-harvest stages. Exogenous plant growth regulators or plant hormone inhibitors has been applied to delay leaf senescence. Modification of related gene expression by over-expression or antisense inhibition could delay or accelerate leaf senescence, and thus influence quality. Environmental factors such as light, temperature and water status also trigger or delay leaf senescence. Delaying leaf senescence could increase chloroplast lifespan and photosynthesis and thus improve source strength, leading to enhanced yield. Accelerating leaf senescence promotes nutrient redistribution from old leaves into young leaves, and may raise yield under certain circumstances. Many genes and transcriptional factors involved in leaf senescence are associated with responses to abiotic and biotic stresses. WRKY transcriptional factors play a vital role in this process and they could interact with JA signalling. This review summarized how genes, plant hormones and environmental factors affect the quality, yield. Besides, the regulation of leaf senescence holds great promise to improving the resistance to plant biotic and abiotic stresses.